Ahmadiyah di Kabupaten Kudus - Moh Rosyid (Balai Penelitian dan Pengembangan Agama Semarang, 2011)
This research was picturing the society of Ahmadiyah (which consistsof only ten families) in Kudus, Central Java. On one hand this community can be so adaptive to outers (non-Ahmadiyah people) such as joining their yasiinan or manaqiban groups and attending neighborhood meetings and can be so exclusive on the other hand. By exclusive here means that the Ahmadiyah people in Kudus will recite the quran and perform daily prayers together with themselves in their own mosque (Ahmadi mosque). The acceptance of Ahmadiyah in Kudus began when in 1989 some people in Kudus looked for physical and spiritual tranquility to Ahmadi people in Gabus, Pati, Central Java. The Ahmadi people of Gabus then taught them sesorah (Ahmadi teachings) which was suitable with them so that the Ahmadi teaching then well received. Kinship and patron client (employer-employee) relationship are two significant factors for the Ahmadiyah recruitment. The Ahmadiyah in Kudus could exist for the “center” (Bogor) sends them religious teachers who teach and lead their daily prayers in their own masjid. This masjid is built on a piece of land given by Ahmadi people. In order for their existence among local people not to be regarded such as creating “water and oil” relationship, Ahmadi people perform some social events which more outers are involved in, such as inviting them to halal bihalal forum and blood donor.